DO THE HUMAN SCIENCE HAVE A SINGLE METHODOLOGY? - Ali Mesbah (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2023)
Despite all serious critiques regarding the appropriateness and sufficiency of empirical methodology in the human sciences, it has secured its place in such researches. Critiques of empiricism in the human sciences take advantage of a variety of strategies to disqualify it and to establish their alternatives. It seems that one key issue which is forgotten or overlooked by these critiques is looking into the nature of the subject matters of the human sciences and their methodological requisites, which can shed some light on the deficiency of empirical methodology in the realm of the human sciences. This article will start with the methodological principle that the appropriate method for studying any subject depends on the nature of its subject matter, which in turn, determines the appropriate research method. On this basis, I will try to analyze the nature of the themes in the human sciences to show the incongruity of empirical method with such concepts. Analyzing such concepts, shows that they represent a variety of conceptual categories such as first intelligibles, secondary philosophical intelligibles, and purely conventional concepts, and to study each one of them, one needs to employ a different methodology. Therefore, the article concludes that empirical method has its limited privileges in studying some of the issues in the human sciences; however, we need to take a multidimensional approach regarding the methodology of the human sciences.